Systemic reflexivity in residential child care: A pedagogical frame to empower professional competence - Formenti, Laura; Rigamonti, Alessandra (International Journal of Child, Youth and Family Studies, 2020)
This position paper offers a pedagogical frame to empower professional work in residential child care. Jobs in this demanding field are characterized by daily relationships with children of different ages, needs, and cultural backgrounds. There is a need for effective communication and interaction with them, their families, co-workers, other professionals, and care agencies, as well as with the larger community. This complexity brings uncertainty and the necessity of thinking and acting in a sensitive way in order to open possibilities for systemic transformation at the micro, meso, and macro levels. In this framework, we focus on reflexivity as a meta-competence — a set of specific postures, competences, and attitudes that characterize expert professional action. A thorough literature review on reflexivity in social work and child protection is aimed at clarifying the meanings, uses, and features of this concept. We claim that systemic reflexivity can be used as a framework, a methodology, and a set of tools to empower professional work by enhancing emotional, cognitive, and epistemic self-awareness, systemic wisdom, abduction, and active listening. To help workers and teams develop these five competences, a self-directed learning module is currently being designed, based on systemic and narrative perspectives, and transformative learning theory.